The experiential aspect of rural home-stay among Chinese and Malay students using diary method - Musa, G.; Kayat, K.; Thirumoorthy, T. (Palgrave Macmillan, 2010)
Tourism involving home-stays is one of the Malaysian government's key efforts to diversify its cultural tourism product. Tourists to the programme are adopted by their foster families experience a more traditional life in Malay villages. Using a diary method, this study examines the experiential aspects of home-stay holidays among domestic students in Kampung Lonek. A total of 19 diaries were content-analyzed using NVivo, which is a qualitative data analysis (QDA) computer software package produced by QSR International. Based on the findings, the home-stay experiential model is developed which explains the different phases of travel experience and their components. The on-site experience reveals three distinct dimensions: ‘environmental experience’, ‘activity, culture and knowledge experience’ and ‘human interaction experience’. The study discusses the differences between Chinese and Malay students in their home-stay experience. The article highlights its methodological, theoretical and managerial contributions.